Tipin Functions in the Protection against Topoisomerase I Inhibitor - Hosono, Yoshifumi (American Society for Biochemistry and Molecular Biology, 2014)
The replication fork temporarily stalls when encountering an obstacle on the DNA, and replication resumes after the barrier is removed. Simultaneously, activation of the replication checkpoint delays the progression of S phase and inhibits late origin firing. Camptothecin (CPT), a topoisomerase I (Top1) inhibitor, acts as a DNA replication barrier by inducing the covalent retention of Top1 on DNA. The Timeless-Tipin complex, a component of the replication fork machinery, plays a role in replication checkpoint activation and stabilization of the replication fork. However, the role of the Timeless-Tipin complex in overcoming the CPT-induced replication block remains elusive. Here, we generated viable TIPIN gene knock-out (KO) DT40 cells showing delayed S phase progression and increased cell death. TIPIN KO cells were hypersensitive to CPT. However, homologous recombination and replication checkpoint were activated normally, whereas DNA synthesis activity was markedly decreased in CPT-treated TIPIN KO cells. Proteasome-dependent degradation of chromatin-bound Top1 was induced in TIPIN KO cells upon CPT treatment, and pretreatment with aphidicolin, a DNA polymerase inhibitor, suppressed both CPT sensitivity and Top1 degradation. Taken together, our data indicate that replication forks formed without Tipin may collide at a high rate with Top1 retained on DNA by CPT treatment, leading to CPT hypersensitivity and Top1 degradation in TIPIN KO cells.